Let's denote the first term of the geometric sequence as \( a_1 \).
Given that the first term is 8 and that each subsequent term is multiplied by \(-38\), we can find the recursive and explicit formulas.
Recursive Formula
- The first term \( a_1 \) is given as: \[ a_1 = 8 \]
- For the recursive definition, we can express the subsequent terms: \[ a_n = a_{n-1} \cdot (-38) \quad \text{for } n \geq 2 \]
So, the complete recursive formula is: \[ \text{Recursive: } a_1 = 8; \quad a_n = a_{n-1} \cdot (-38) \text{ for } n \geq 2 \]
Explicit Formula
The explicit formula for the \( n \)-th term of a geometric sequence can be expressed using the formula: \[ a_n = a_1 \cdot r^{n-1} \] where \( a_1 \) is the first term and \( r \) is the common ratio (which is \(-38\) in this case).
- Substituting the values: \[ a_n = 8 \cdot (-38)^{n-1} \]
So, the complete explicit formula is: \[ \text{Explicit: } a_n = 8 \cdot (-38)^{n-1} \]
Summary
- Recursive: \( a_1 = 8; ; a_n = a_{n-1} \cdot (-38) \text{ for } n \geq 2 \)
- Explicit: \( a_n = 8 \cdot (-38)^{n-1} \)